A Study on Sociodemographic Profile and Comparison of Pattern of Facial Injuries in Victims of Two Wheeler Road Traffic Accident with and without usage of Helmet in South Chennai - P. Shruthi1, R.Venkat2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background and Aim: Road traffic accident a cause of unnatural death is the third major preventable oneamongst all death. Maxillofacial trauma is often encountered in accidents either as isolated injury or alongwith several injuries to the head, neck, chest and abdomen.Materials and Method: A retrospective observational study was conducted in the Department of ForensicMedicine and Toxicology at Saveetha Medical College between January 2018 to December 2018 with anobjective to analyse the Sociodemographic profile and compare the pattern of facial injuries in Road TrafficAccident cases with and without helmet usage.Results: Out of total 2438 RTA cases analysed, 1523 were two wheeler RTAs (62.5%). Amongst 1523cases,173 (11.36%) had facial injuries. The peak incidence of maxillofacial injuries (42.7%) was observed inthe age group of 21 to 30 years, with males outnumbering females in all age groups. The maximum numberof trauma cases was reported in late evening hours. Maximum RTAs occured in the months of winter usuallyin the semi urban areas. The injuries were sustained mostly due to frontal impact. Injuries to lip particularlylaceration injuries were most frequent. Injuries occured most commonly to the riders. The injuries were seenmore amongst the non helmet usage cases amounting to 68% of cases.Conclusion: The changing trend of etiology of maxillofacial injuries due to Road traffic Accidents inChennai necessitates strict traffic legislation and better health care facilities with respect to maxillofacialunits.